Evaluation of the SLICS use in the treatment of subaxial cervical spine injuries - Halisson Y. F. da Cruz; Andrei F. Joaquim; Helder Tedeschi; Alpesh A. Patel (Arquivos de Neuro-Psiquiatria)
The SLICS (Sub-axial Cervical Spine Injury Classification System) was proposed to help in the decision-making of sub-axial cervical spine trauma (SCST), even though the literature assessing its safety and efficacy is scarce. Method We compared a cohort series of patients surgically treated based on surgeon’s preference with patients treated based on the SLICS. Results From 2009-10, 12 patients were included. The SLICS score ranged from 2 to 9 points (mean of 5.5). Two patients had the SLICS < 4 points. From 2011-13, 28 patients were included. The SLICS score ranged from 4 to 9 points (mean of 6). There was no neurological deterioration in any group. Conclusion After using the SLICS there was a decrease in the number of patients with less severe injuries that were treated surgically. This suggests that the SLICS can be helpful in differentiating mild from severe injuries, potentially improving the results of treatment.